1997
DOI: 10.1023/a:1018431104786
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: To assess more precisely the relative risks associated with established risk factors for breast cancer, and whether the association between dietary fat and breast cancer risk varies according to levels of these risk factors, we pooled primary data from six prospective studies in North America and Western Europe in which individual estimates of dietary fat intake had been obtained by validated food-frequency questionnaires. Based on information from 322,647 women among whom 4,827 cases occurred during follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(11 citation statements)
references
References 27 publications
2
8
0
1
Order By: Relevance
“…These findings are in line with other studies [5] [6]. Breast cancer shows a strong linked to the early age of menarche and additional years for age at menarche decreased by 5% risk of developing breast cancer [7]. The most convincing explanation for the latter remains the hormonal impregnation that exists during the period of activity of the ovaries [8].…”
Section: Discussionsupporting
confidence: 91%
“…These findings are in line with other studies [5] [6]. Breast cancer shows a strong linked to the early age of menarche and additional years for age at menarche decreased by 5% risk of developing breast cancer [7]. The most convincing explanation for the latter remains the hormonal impregnation that exists during the period of activity of the ovaries [8].…”
Section: Discussionsupporting
confidence: 91%
“…: 5% decrease in risk per 1-year delay after age 12) and menopause (e.g. : 3% increase in risk per 1-year delay age at menopause)[8,9,18]. In contrast, we observed a fairly uniform decreased risk with older ages at menarche and a non-significant increased risk only in the oldest age-at-menopause group.…”
Section: Discussionmentioning
confidence: 49%
“…Clinical, epidemiological, and laboratory studies have suggested EDCs are associated with earlier pubertal events [ 6 ] and timing of pubertal maturation is associated with breast cancer risk [ 7 ]. For every 1-year delay in menarche, the risk of breast cancer decreases by around 5% [ 8 , 9 ]. Further, certain EDCs are important breast carcinogens that may impact breast tissue remodeling, which in turn may affect mammographic breast density [ 10 ], a measure of the amount of fibroglandular breast tissue and one of the strongest risk factors for breast cancer [ 11 – 13 ].…”
Section: Introductionmentioning
confidence: 99%